2021
DOI: 10.3390/ijms23010150
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxytocin in Stress Responses, Allostasis and Resilience

Abstract: Oxytocin has been revealed to work for anxiety suppression and anti-stress as well as for psychosocial behavior and reproductive functions. Oxytocin neurons are activated by various stressful stimuli. The oxytocin receptor is widely distributed within the brain, and oxytocin that is released or diffused affects behavioral and neuroendocrine stress responses. On the other hand, there has been an increasing number of reports on the role of oxytocin in allostasis and resilience. It has been shown that oxytocin ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 233 publications
(274 reference statements)
1
41
0
1
Order By: Relevance
“…The promoting effects of stress on social interaction were observed in WT mice of both sexes and may be explained by multiple hypotheses. One possible explanation lies in the prosocial effects of increased oxytocin, since this has been described in hypothalamic and limbic brain regions following exposure to a variety of stressors 63 . A second possible interpretation may consider the increased social interaction of WT stressed mice as a reflection of a the altered excitatory/inhibitory(E/I) imbalance induced by stress especially in brain circuits involving the prefrontal cortex 15 , 64 , known to critically control social behaviors in rodents 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…The promoting effects of stress on social interaction were observed in WT mice of both sexes and may be explained by multiple hypotheses. One possible explanation lies in the prosocial effects of increased oxytocin, since this has been described in hypothalamic and limbic brain regions following exposure to a variety of stressors 63 . A second possible interpretation may consider the increased social interaction of WT stressed mice as a reflection of a the altered excitatory/inhibitory(E/I) imbalance induced by stress especially in brain circuits involving the prefrontal cortex 15 , 64 , known to critically control social behaviors in rodents 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that the role of oxytocin is best characterised through allostasis; as it can help facilitate the dynamic adjustment and consolidation of homoeostatic setpoints, and is crucial to many of life’s essential survival needs ( Quintana and Guastella, 2020 ). Therefore, the effective activation of the oxytocin system could help achieve positive physical and psychological clinical results through its ability to help patients adapt and encourage successful recovery ( Takayanagi and Onaka, 2021 ). Additionally, oxytocin can help with analgesia due to its connection with decreased activity in the AIC in response to noxious stimuli, regulation of noxious threats, and increased activity in the prefrontal lobe ( Kreuder et al, 2019 ).…”
Section: The Role Of Touch In Developing a Connectionmentioning
confidence: 99%
“…Thus, stimuli that can be interpreted by the subject as potentially dangerous, such as the presence of a stranger or a person with traits that suggest mistrust, or a hostile environment, will trigger a completely different oxytocin-mediated reaction compared to the presence of either a very close person or positive facial expressions that indicate a friendly environment. The fact that oxytocin can cause different reactions depending on how the environment is perceived by the subject is based on the hypothesis that oxytocin plays its role indirectly, orchestrating the activity of several neurotransmitter systems [ 38 , 39 ].…”
Section: Connections Between Oxytocin and Neurotransmitters In Affect...mentioning
confidence: 99%